Effect of recombinant transglutaminase on the quality characteristics of cooked beef meatballs - Fatma ERSÖZ; Elif AYKIN DİNÇER; Aysun Türkanoğlu ÖZÇELIK; Mehmet İNAN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
Transglutaminase (TGase) is an enzyme widely used in the food industry. In this study, the eff ect of transglutaminase enzyme on the chemical and physical characteristics of cooked beef meatballs was evaluated. For this aim, beef meatballs were prepared by using recombinant microbial transglutaminase (MTGase) and commercial TGase enzymes, after that physical and chemical tests were applied to meatball samples. The addition of MTGase enzyme improves the quality parameters of the beef meatballs. The myofibrillar proteins of cooked meatball samples were also analyzed with SDS-PAGE analysis. It was observed that, actin and myosin proteins bind covalently to form a new high molecular weight protein by the help of MTGase addition. These results indicated that recombinant MTGase enzyme can be used to obtain high quality restructured beef meat products.